Against Self-ownership: A Philosophical Reflection - Qusthan Firdaus (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2019)
This paper argues that the libertarians simply cut off the contingency (between not-yet-persons and persons) into time-slice account. They do not want to deal with a problem such as: how could the structure of Self-Ownership (SO) embed in persons? Indeed, the libertarians arbitrarily ignore who the owner of not-yet-persons is if a child is not a person yet. On the other hand, if God confers people’s property in person, it consequently means that a believer of SO is supposed to also believe in God. Insofar as a believer of SO cannot explain what the source of SO is, he needs to rely on a Lockeian explanation where God confers human with a property in person. There are two general libertarian reasons for this. First of all, the libertarian notion of slavery, as Cohen encounters it. Secondly, as Narveson conceives, since each individual has separate life, therefore every interaction between individuals is supposed to be based on mutual benefits. Therefore, the more appropriate way to encounter the thesis of SO is by cutting the bridge between the notion of owning self and a matter of moral right. Instead of cutting the bridge, Cohen widens his rejection by proposing another institution. Nevertheless, Cohen does nothing to explain what the structure of the bridge consist in and what the foundation for such a bridge is.